How Do Cells of the Oligodendrocyte Lineage Affect Neuronal Circuits to Influence Motor Function, Memory and Mood? - Pepper, Renee E.; Pitman, Kimberley A.; Cullen, Carlie L.; Young, Kaylene M. (Frontiers in Cellular Neuroscience, 2018)
Oligodendrocyte progenitor cells (OPCs) are immature cells in the central nervous system (CNS) that can rapidly respond to changes within their environment by modulating their proliferation, motility and differentiation. OPCs differentiate into myelinating oligodendrocytes throughout life, and both cell types have been implicated in maintaining and modulating neuronal function to affect motor performance, cognition and emotional state. However, questions remain about the mechanisms employed by OPCs and oligodendrocytes to regulate circuit function, including whether OPCs can only influence circuits through their generation of new oligodendrocytes, or can play other regulatory roles within the CNS. In this review, we detail the molecular and cellular mechanisms that allow OPCs, newborn oligodendrocytes and pre-existing oligodendrocytes to regulate circuit function and ultimately influence behavioural outcomes.